Requirements analysis for transformation of urban district into smart city-a case study of Sri Gading - Muhammed Asri, Noor Athirah; Ibrahim, Rosziati (WARSE, 2021)
Sri Gading is an urban district located in Batu Pahat, Johor. Sri Gading has few elements that can be used to transform the place into smart city. This paper presents the requirements analysis of the survey at Sri Gading for realization of transforming an urban district into a smart city. The model of smart city consists of four elements which are infrastructures, IOTs, environment and culture. This paper will also highlight the results of the requirements analysis from the survey instrument of Sri Gading. The preliminary study for questionnaire design, sample size, pilot study and questionnaire response rate will also be discussed in this paper.